Analysis of domain specific modeling languages for strategy educational games design - Nurhadi, N.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Educational games are serious games that specifically used for education yet it is fun to play. There are numbers of domain specific modeling languages for educational games focus in various aspect and theories of learning. By having domain specific modeling language which applies a visual diagramming language, it helps in represent design ideas and logic. This paper analyzes existing modelling languages to assess the coverage of strategy genre and transfer learning concepts. The results show that existing modelling languages covers important strategy genre concepts but cover very little of the transfer learning concepts. The authors conclude that the existing modelling languages can be used to model small strategy games but will have trouble to scale to large strategy games, and will not be able to model games that guarantee students learning. Â© 2016 IEEE.